POTENCIAL DA MADEIRA DE Pterogyne nitens Tul. (MADEIRA-NOVA) PARA PRODUÇÃO DE CARVÃO VEGETAL - Márcio Emanuel Oliveira Figueiredo; Dalton Longue; Allana Katiussya Silva Pereira; Angélica de Cássia Oliveira Carneiro; Carlos Miguel Simões da Silva (Ciência Florestal, 2018)
The low diversity of forest tree species used in the formation of planted forests in Brazil, based mainly on Eucalyptus and Pinus genus, has led to study of alternative woods that show good productive potential. Thus, Pterogyne nitens species (madeira-nova), which shows good growth in Brazil’s northeast region, it has aroused interest despite little research on their technological characteristics. The objective of this study was to analyze the potential of Pterogyne nitens wood for the charcoal production. Nine-year-old timbers were harvested in Vitória da Conquista town, Bahia state. The woods were fragmented and carbonized in a muffle furnace with electric heating and final temperatures of 300°C, 450°C and, 600°C. Analysis were performed of carbonization process (yield in charcoal, condensable gases and non-condensable gases), apparent density (0% moisture), friability, superior heating power and, immediate chemistry of charcoal. Based on the results, it could be concluded that the fixed carbon and superior heating value of produced charcoal increased with the increasing of the final carbonization temperature. On the other hand, the increasing of the final carbonization temperature caused a reduction in the content of volatile materials and charcoal yield. The yield of non-condensable gases and friability of charcoal increased with the elevation of final carbonization temperatures from 300ºC to 450ºC, remaining constant to higher temperatures. Finally, the final carbonization temperature of 450°C was considered optimal for carbonization of that studied wood.